DO TEACHERS HAVE ADEQUATE ICT RESOURCES IN PROMOTING ENGLISH LANGUAGE TEACHING AND LEARNING? (Journal of Information and Communication Technology, 2006)
It is generally acknowledged that the standard of English in Malaysian schools has been deteriorating over the years. This decline must be put right if we are to maintain our competitiveness in the global market. The on-going ICT revolution has dramatically changed the way teachers teach and students learn and the appropriate use of ICT resources can give a tremendous boost to the teaching and learning of English. Traditional classroom teaching ought to be complemented by providing a web-based learning environment. This research is based on the findings of a questionnaire survey conducted over a period of five months (i.e. from 1st September 2004 to 31stJanuary 2005). According to the findings 72.4 % of the respondents say that there is a lack of ICT resources in schools. More recently however, the supply of ICT resources in the schools have increased by leaps and bounds but yet the use of ICT tools in English Language teaching and learning is far from satisfactory. In the concluding part of this article, some obvious obstacles to ICT use in the teaching and learning of English are discussed.